Overview of Knowledge in Patients with Hypertension for Stroke Prevention at the Work Area of the Kejobong Health Center: Gambaran Pengetahuan pada Penderita Hipertensi dalam Upaya Pencegahan Stroke di Wilayah Kerja Puskesmas Kejobong - Rahmawati, Tartib Qodriah; Waladani, Barkah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Hypertension is a condition of the blood vessels can inhibit the supply of oxygen and vitamins carried by the blood, so that they don’t reach the body tissues that need them with signs of headache, fatigue, shortness of breath, anxiety and decreased consciousness. The death rate due to hypertension and stroke continues to increase every year, 427,218 cases of death due to hypertension in Indonesia and 5.5 million cases of death due to stroke. Based on the consequences of the prevalence of stroke sufferers and related hypertension and every year there is an increase in both, so the knowledge of high blood pressure sufferers on stroke prevention is very important. To identified of knowledge in people with hypertension for stroke prevention at the working area of the Kejobong Health Center. Using quantitative with a descriptive observational design. The research instrument used a modified SKT (Stroke Knowledge Test) questionnaire. The research respondents were 84 people. Data is processed with SPSS-25. It was obtained an overviewoverview of stroke prevention in hypertension sufferers in the working area of the Kejobong district health center with the result that they had less knowledge with a total of 79 respondents (94.0%). The level of knowledge of stroke prevention efforts in hypertensive patients in the working area of the Kejobong district health center has a low level of knowledge. Future researchers can develop this research with different methods and can examine the factors that influence the level of knowledge in prevent stroke in people with hypertension.